Impact of Andropause on Multiple Sclerosis - Ysrraelit, Maria C.; Correale, Jorge (Frontiers in Neurology, 2021)
Andropause results from the natural decrease in testosterone levels that occurs with age. In contrast to menopause, which is a universal, well-characterized process associated with absolute gonadal failure, andropause ensues after gradual decline of both hypothalamic-pituitary-gonadal axis activity, as well as of testicular function, a process which usually develops over a period of many years. Increasing evidence on greater risk of MS associated with lower testosterone levels is being reported. Likewise, epidemiological studies have shown a later age of onset of MS in men, relative to women, which could perhaps respond to the decline in protective testosterone levels. In this review, we will discuss the role of androgens in the development and function of the innate and adaptive immune response, as well as in neuroprotective mechanisms relevant to MS. Testosterone effects observed in different animal models and in epidemiological studies in humans will be discussed, as well as their correlation with physical disability and cognitive function levels. Finally, published and ongoing clinical trials exploring the role of androgens, particularly at key stages of sexual maturation, will be reviewed.